2016
DOI: 10.1017/ice.2016.252
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Necessity of Training for Optimal Personal Protective Equipment Use

Abstract: Healthcare workers routinely self-contaminate even when using personal protective equipment. Observations of donning/ doffing practices on inpatient units along with surveys were used to assess the need for a personal protective equipment training program. In contrast to low perceived risk, observed doffing behaviors demonstrate significant personal protective equipment technique deficits. Infect Control Hosp Epidemiol 2017;38:226-229.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 4 publications
1
27
0
4
Order By: Relevance
“…Others have found that workers desire hands-on training about PPE donning and doffing, and this type of training is consistent with principles of adult education because it actively engages the worker in a realistic, relevant activity. [32][33][34] Hands-on training also offers opportunity for evaluation, which is particularly important when self-perceived proficiency is not correlated with performance, such as has been observed for doffing of PPE ensembles. [35] Hands-on training can provide real-time feedback to correct behaviors in the moment with observer interventions or surrogates for contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that workers desire hands-on training about PPE donning and doffing, and this type of training is consistent with principles of adult education because it actively engages the worker in a realistic, relevant activity. [32][33][34] Hands-on training also offers opportunity for evaluation, which is particularly important when self-perceived proficiency is not correlated with performance, such as has been observed for doffing of PPE ensembles. [35] Hands-on training can provide real-time feedback to correct behaviors in the moment with observer interventions or surrogates for contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Personal protective equipment (PPE) is clothing and equipment worn to protect employees, used in jobs that involve exposure to hazards, including infectious materials (Lau et al, 2004). PPE for infection control includes gloves, masks, respirators, face and eye protection, gowns, and shoe and head covers (Doll et al, 2017). For example, a physician might wear a mask, eye protection, and a gown when examining a patient to protect their face and clothing from exposure to infection.…”
Section: Wearing Protective Equipmentmentioning
confidence: 99%
“…Specific standards exist for correctly wearing, removing, and cleaning various types of PPE used for infection control, and small errors can lead to a dramatic increase in the spread of infectious diseases (Lau et al, 2004). Even in healthcare, a business sector familiar with the use of infection-control PPE, compliance with PPE use and procedures is often lacking (Doll et al, 2017;Mumma et al, 2018;Schumacher et al, 2015;Tomas et al, 2015). Phan et al (2019) observed that 90% of observed PPE doffing was completed incorrectly by healthcare workers.…”
Section: Wearing Protective Equipmentmentioning
confidence: 99%
“…PPE protects the wearer and contributes to preventing further transmission, yet is often inappropriately used, especially by doctors (6,7). Many doctors feel that they have inadequate knowledge and practical skills, in IPC, generally, and PPE use, speci cally (8), suggesting an unmet need for teaching undergraduates about its importance (9). Mann and Wood found that around 50% of medical students thought their course should have had a greater emphasis on IPC (10), while John et al reported that 92.5% of medical students made procedural errors when removing PPE during training (11).…”
Section: Introductionmentioning
confidence: 99%